Malaysia and the law of outer space / Tunku Intan Mainura Tunku Makmar Nizamuddin - Tunku Makmar Nizamuddin, Tunku Intan Mainura (Faculty of Administratron and Law, 2004)
"I wish to reaffirm Malaysia's commitment to the development and advancement of space science and technology applications. However, aware of the fact that Malaysia is a new participant in the space arena and conscious of the limitations of its resources, we will seek International cooperation in all aspects of space activities while at the same time vigorously nurturing our own indigenous capability".